Der expressive Elan in der Malerei nach 1945 - Schmalenbach, Werner (Duisburg : Franz Haniel & Cie., 1987)
Bissier, Julius ; Brüning, Peter ; Buchheister, Carl ; Dahmen, Karl Fred ; Fautrier, Jean ; Götz, Karl Otto ; Hartung, Hans ; Hoehme, Gerhard ; Mathieu, Georges ; Nay, Ernst Wilhelm ; Nitsch, Hermann ; Platschek, Hans ; Rainer, Arnulf ; Schultze, Bernard ; etc.
Duits & Engels
boek